A Bioecological Study of the Fresh-Water Sponges of Hammond Bay, Lake Huron - Lukasiewicz, Joseph (University of Wisconsin-Stevens Point, 1978)
A bioecological study of Eunapius fragilis, Heteromeyenia tubisperma, Heteromeyenia baileyi, Ephydatia fluviatilis, and Ephydatia mulleri was conducted in the vicinity of Hammond Bay (Michigan), Lake Huron, from September 1976 to November 1977. All five species were found encrusted on various wood substrates in a shallow, seasonally inundated pond adjacent to the bay. E. fragilis was the only species collected from the rock-cobble eulittoral zone of the lake. A synopsis of the distribution of fresh-water sponges in the St. Lawrence Great Lake system; observations on the timing of life cycle events, spicule size-distributions, and associated organisms; and a revision of the physiological ranges of the above species are presented.